Studi Eksploratif Untuk Mengidentifikasi Faktor-Faktor Retensi Modifikasi Video Gim - Hendrasto, Ferdian; Juliadilla, Risa; Aprilia, Mitha Endah (Jurnal Ekonomi Manajemen Perbankan, 2024)
Prosumption is a form of co-creation activity performed by customer. In video gim, an interesting form of presumption is modifikasi gim. An activity in which a person manipulates an aspect or the entirety of a gim, and then release the mod to public free of charge. Mod extend the life of video gim. Many research was conducted in this field, but the main drivers of why people are willing to invest their time and effort to develop mod are not well identified. This research found that those drivers are personal enjoyment, curiosity and learning, social affiliation, and recognition or appreciation.